THE ROLE OF LOCAL WISDOM IN THE DEVELOPMENT OF HERITAGE TOURISM AT THE LIYANGAN SITE, TEMANGGUNG DISTRICT - Septarini, Vira (SABA: Journal of Tourism Research, 2024)
Local wisdom, as a result of community experiences in interacting with their environment, provides solutions to various challenges. Local wisdom emerges from the customary, religious, and cultural values that are an integral part of a community. The dimensions of local wisdom include knowledge, values, skills, resources, decision-making mechanisms, and community within the context of the local society. The role of local wisdom is crucial in the development of cultural heritage tourism to enhance awareness and positive attitudes towards environmental and cultural preservation. Examples of applying local wisdom, such as the water canal system in the Newari Site, Nepal, and the Subak irrigation in Bali, Indonesia, illustrate the significant value of cultural heritage for visitors. However, the development of cultural heritage tourism must consider local wisdom and sustainability principles, including environmental sustainability, equitable development, fair economic growth, and community security. Liyangan Village in Temanggung Regency, Indonesia, offers diverse local wisdom with the potential of an attractive archaeological site, the Liyangan Site. However, the challenges in its development are not in line with local wisdom and existing master plans. Therefore, this research aims to understand the role of local wisdom in the development of heritage tourism at the Liyangan Site and evaluate its alignment with sustainability principles. Through a descriptive qualitative approach, this study identifies and analyzes the role and forms of local wisdom in the context of the Liyangan Site. The research findings indicate that local wisdom indirectly plays a fundamental role in the development of heritage tourism at the Liyangan Site by reducing the impacts on environmental and cultural degradation. This research makes a significant contribution to supporting sustainable cultural heritage tourism development by applying appropriate local wisdom at the Liyangan Site, Liyangan Village.